SERPENT-Brasil: a technological tool for snakebite management - Jacqueline de Almeida Gonçalves Sachett; Gisele dos Santos Costa Rocha; Elisangela Silva; Anne Grace Andrade da Cunha Marques; Pedro Ferreira Bisneto; Handerson Silva Pereira; Victor Carlos Pardo Ratis da Silva; Kathleen Maclenny Pereira Carvalho; Lincoln Luís Silva; Manuela Berto Pucca; Wuelton Marcelo Monteiro (Revista Panamericana de Salud Pública)
Objective. To report on the development and features of a mobile application (app) to guide the public and health professionals on pre-hospital emergency measures after snake envenomation. Methods. This was a four-stage methodological study conducted from June 2020 to July 2022. The app development included creating a mobile resource to guide pre-hospital care and to direct victims to hospitals that have antivenom. Results: The SERPENT-BRASIL app was developed for use on Android and IOS devices with an intuitive interface. It offers online and offline access to information on hospitals and mapping routes via Google Maps. In addition, it allows users to report snake sightings and to request emergency rescue. Conclusion: The SERPENT-BRASIL app improves snakebite management and prevention, eases the burden on health services, and promotes health education. Collection of snake envenomation data contributes to public safety, making the app an essential resource for public safety in Brazil.